mRNA Transfection of Mouse and Human Neural Stem Cell Cultures - McLenachan, Samuel (Public Library of Science, 2013)
The use of synthetic mRNA as an alternative gene delivery vector to traditional DNA-based constructs provides an effective method for inducing transient gene expression in cell cultures without genetic modification. Delivery of mRNA has been proposed as a safer alternative to viral vectors in the induction of pluripotent cells for regenerative therapies. Although mRNA transfection of fibroblasts, dendritic and embryonic stem cells has been described, mRNA delivery to neurosphere cultures has not been previously reported. Here we sought to establish an efficient method for delivering mRNA to primary neurosphere cultures. Neurospheres derived from the subventricular zone of adult mice or from human embryonic stem cells were transfected with EGFP mRNA by lipofection and electroporation. Transfection efficiency and expression levels were monitored by flow cytometry. Cell survival following transfection was examined using live cell counting and the MTT assay. Both lipofection and electroporation provided high efficiency transfection of neurospheres. In comparison with lipofection, electroporation resulted in increased transfection efficiencies, but lower expression per cell and shorter durations of expression. Additional rounds of lipofection renewed EGFP expression in neurospheres, suggesting this method may be suitable for reprogramming applications. In summary, we have developed a protocol for achieving high efficiency transfection rates in mouse and human neurosphere cell culture that can be applied for future studies of gene function studies in neural stem cells, such as defining efficient differentiation protocols for glial and neuronal linages.